The use of generic immunosuppression for transplant patients: a UK perspective. Issue 5 (19th July 2013) - Devaney, Andrea; Lee, Mark
Abstract : Generic immunosuppression is not a new phenomenon to solid organ transplantation; however, clinical and patient safety concerns have been raised with the introduction onto the market of multiple brands of generic ciclosporin, tacrolimus and mycophenolate mofetil. In the UK there are significant national drivers to support efficiency savings within the National Health Service (NHS) and thus allow reimbursement back into clinical services to continually improve quality of patient care. The use of generic immunosuppression to release such savings must be given serious consideration. In the UK, many transplant centres have safely implemented the use of generic tacrolimus and mycophenolate mofetil brands into clinical practice in both de novo and established renal transplant recipients.